Dampak Transformasi Digital pada Kinerja UMKM di Indonesia - Adi Pradana, Muhammad Rafieq; Parela, Epi; Pramana Putra, Nanda; Junaidi (LPPM STIE KRAKATAU, 2024)
This research examines the impact of digital transformation on the performance of MSMEs in Indonesia through secondary data analysis from various published studies. Digital transformation, which includes the use of digital technology to change business processes and interactions with customers, has become the key to maintaining the competitiveness of MSMEs in the digital era. Analysis was carried out on the factors that influence the success of digital transformation and its impact on MSME performance. The main findings of this research show that leadership behavior and formality have a significant influence on the use of digital media, while entrepreneurial leadership directly and indirectly influences the performance of MSMEs. Digital marketing and marketing capabilities have also been proven to improve MSME performance. In addition, digital literacy plays an important role in supporting digital transformation and the competitiveness of micro and small businesses. The COVID-19 pandemic has accelerated the adoption of digital technology by MSMEs, which has had a positive impact on their performance. Digital transformation models adapted to the specific conditions of MSMEs during the pandemic have proven effective in accelerating the transformation process and improving performance. Ecosystem-based digital platforms help MSMEs integrate strategic knowledge sources and respond to dynamic environmental changes, increasing their innovation and competitiveness in the global market